Three-dimensional geoelectrical model of the central part of the Zvizdal-Zaliska and Brusyliv fault zones of the Ukrainian Shield - Т.К. Бурахович; В.А. Ільєнко; А.М. Кушнір (Геофизический журнал, 2023)
To study the deep structure of the geoelectrically complex junction zone of three megablocks of the western part of the Ukrainian Shield (Volyn', Podil, and Ros'), a three-dimensional model of the central part of the Zvizdal-Zaliska and Brusyliv fault zones was created. It is based on modern experimental observations of the Earth's natural low-frequency electromagnetic field in a wide range of periods. Synchronous experimental data of deep magnetotelluric sounding and magnetovariational profiling, obtained by the Institutes of the National Academy of Sciences of Ukraine in 2009—2019, were analyzed. The main issues of the geoelectrical modeling methodology using the Mtd3fwd software complex were considered, such as model elements, stages, alternative models, examples of calculations and comparison of observations, errors, etc. The constructed model analysis showed that of the large number of near-surface anomalies with low resistivity (5 to 100 Ohm · m), most sink to 500 m and only a few reach a depth of 1 km and are followed up to 11 km. It was established that there are connections between conductivity and structural features of the Zvizdal-Zaliska, Brusyliv, Nemyriv fault zones, the Samgorod fault and the Kocheriv synclinorium. Most of the isolated conductors appear in a mosaic pattern along the extended fault zones and form interspersed chains of high and low resistivity. Regional anomalies were confirmed and detailed both in the deep part of the crust and in the upper mantle; part of the Zvizdal-Zaliska fault zone appeared at depths of 15—30 km as a contact zone of abnormally high and low resistivities. Anomalies are confined to elongated zones of metasomatization and graphitized rock areas, some of the surface anomalies correspond to areas of the weathering crust. Most of the anomalies coincide with ore occurrences, ore-bearing fields and mineral deposits. The conducted geological-geoelectrical analysis of the model made it possible for the first time to identify two promising areas for further study that meet the geoelectrical criteria for the mineral search: along the Zvizdal-Zaliska fault zone between the Samgorod and Unava faults; along the Samgorod fault in the area of its intersection with the Kocheriv and Taboriv faults.